Design to Build a Mobile Android-Based Mathematics Learning Application for PAUD Kartini - Nungsiyati Nungsiyati; Indrianingsih Indrianingsih (STMIK Pringsewu, 2023)
Applications are often also referred to as software, which is a computer program whose instructions can be changed easily. The purpose of this research is to make a Mathematics Learning Application in more interesting way based on Mobile Android. The application is made using SDLC (System Development Life Cycle) method. SDLC is one of the popular information system development methods when the information system was first created. The results of the design of the mathematics learning application at PAUD Kartini include learning numbers, learning addition, learning subtraction, practicing questions, and exit menus. Existing facilities are very helpful in learning.